The calcium: an early signal that initiates the formation of the nervous system during embryogenesis - Leclerc, Catherine; Moreau, Marc; Néant, Isabelle (Frontiers in Molecular Neuroscience, 2012)
The calcium (Ca2+) signaling pathways have crucial roles in development from fertilization through differentiation to organogenesis. In the nervous system, Ca2+ signals are important regulators for various neuronal functions, including formation and maturation of neuronal circuits and long-term memory. However, Ca2+ signals are also involved in the earliest steps of neurogenesis including neural induction, differentiation of neural progenitors into neurons, and the neuro-glial switch. This review examines when and how Ca2+ signals are generated during each of these steps with examples taken from in vivo studies in vertebrate embryos and from in vitro assays using embryonic and neural stem cells (NSCs). During the early phases of neurogenesis few investigations have been performed to study the downstream targets of Ca2+ which posses EF-hand in their structure. This opens an entire field of research. We also discuss the highly specific nature of the Ca2+ signaling pathway and its interaction with the other signaling pathways involved in early neural development.